Comparison of histological and molecular diagnosis of Helicobacter pylori in benign lesions and gastric adenocarcinoma - Cesar, ACG; Cury, P. M.; Payao, SLM; Liberatore, P. R.; Silva, A. E. (Springer, 2005)
Helicobacter pylori colonization is associated with chronic gastritis, peptic ulcers, intestinal metaplasia, adenocarcinoma and lymphoma of the stomach. The objective of this study was to compare the results of the routinely used histology with molecular diagnosis for the detection of H. pylori. Eighty samples from gastric lesions (chronic gastritis, atrophic gastritis, gastric ulcer, and intestinal metaplasia), 18 gastric adenocarcinoma and 10 normal mucosa H. pylori-negative (control) samples were obtained. All samples were examined histologically (hematoxylin-eosin and Giemsa staining), and PCR amplifications of the species-specific antigen gene (H3H4) and urease A gene segment (H5H6) of H. pylori were made, using the human gene CYP1A1 for DNA quality control. In the benign lesion and adenocarcinoma the infection was detected in 43% (42/98) and 71% (70/98) by histological and molecular diagnosis (p=0.0001), respectively. The PCR test detected H. pylori in 27.5% (22/80) of the benign gastric lesions and in 50% (9/18) of the gastric adenocarcinoma cases, the histological diagnosis being negative for this bacterium. About 2.5% of the samples, exclusively from benign lesions and with a positive histological diagnosis, showed negative molecular results for both primers. Statistically significant differences were found between the histological and the molecular method in intestinal metaplasia (p=0.0461) and gastric adenocarcinoma (p=0.0011), due to underdetection of H. pylori by the histological method, which is probably due to the low density of the bacterium as a consequence of the severe atrophy of the gastric mucosa. Our findings suggest that PCR is the more efficient method for the assessment of H. pylori infection, especially in metaplasia and gastric adenocarcinoma.
Keywords: Helicobacter pylori; gastric lesions; adenocarcinoma; histological diagnosis; PCR